KOMPARASI KONSEP KEADILAN MENURUT ARISTOTELES DAN IMAM SYAFI’I: TELAAH FILOSOFIS DAN YURIDIS - Evan Sebastian Silaen; Hasna Qotrunnada Fitri; Raditya Dzaky Nurseha; Gerlavista Elena Zuafris; Nadine Aura Kamila (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the role of the principles of ushul fiqh—such as maslahah, istihsan, qiyas, and sadd al-dzari‘ah—in shaping the concept of justice in Islamic law, and to compare them with the thoughts of Aristotle and Imam Shafi’i on justice. The method used is qualitative research with a normative-philosophical approach through a literature study of classical and modern literature. The results of the study indicate that Aristotle views justice as proportional balance and distribution based on individual merit, while Imam Shafi’i positions justice as the embodiment of Divine will based on texts and sharia. Usul fiqh functions as a methodological bridge that allows Islamic law to integrate rationality and transcendental values ​​in responding to social reality. The conceptual contribution of this study lies in the affirmation that justice in Islamic law is not merely legal-formal, but also encompasses moral, spiritual, and social dimensions, thus being able to maintain a balance between legal certainty and the welfare of the people and remain relevant in facing the dynamics of modern life.